Solar Panel Installation Analysis: A Case Study Wangi-Wangi, Wakatobi, Indonesia - Darmana T.; Iwan Tutuka P.; Rizki Pratama P.; Suyanto H.; Rahayu S.; Hidayat R.; Abidin A.A.B.Z.; Renuga A.; Verayiah P. (Institute of Electrical and Electronics Engineers Inc., 2025)
This paper presents a comprehensive calculation analysis of solar panel installation on Wangi-Wangi Island, Wakatobi Regency, evaluating parameters such as installation expenses, net present value (NPV), and payback duration. The unique geographical isolation of Wangi-Wangi Island makes it an ideal case study for assessing the feasibility and effectiveness of renewable energy technologies. By systematically evaluating historical load data and projecting future energy demands, the analysis revealed that a total capacity of 4.6672 MWp is required, with an installation area of approximately 2.6594 hectares (0.030452% of the island's total area). The projected energy production is 9.3345 MWh per day, requiring over 23,000 panels. The financial analysis estimates an installation cost of Rp70,011,000,000 and annual maintenance expenses of Rp933,480. Despite significant energy savings of Rp12,084,949.64 per year, the payback period is approximately 6,278 years, with an NPV of Rp-69,895,251,558.48, indicating substantial financial challenges. While the transition to renewable energy is essential for sustainable development on remote islands like Wangi-Wangi, the high upfront costs and lengthy payback period pose significant financial barriers. Comprehensive financial planning and strategic decision-making are crucial to ensure the viability and sustainability of such projects. ? 2024 IEEE.